Postprandial Lipid Abnormalities in Type 2 Diabetes Mellitus, A Study at NGMC, Kohalpur - Shukla, Avikal (Journal of Nepalgunj Medical College, 2017)
Aim and Objectives: To study the postprandial lipid abnormalities in patients with type 2 diabetes mellitus. Material and Methods : Postprandial lipids were studied in 40 male type 2 diabetic subjects (age 49.75 ± 4.82 years) and 40 age and sex matched healthy controls (age 49.55 ± 4.82 years) after an oral fat challenge which consisted of a meal providing 729 kcal/m2 body surface area with 68 gm fat. Results: Average duration of diabetes among diabetic was 2.32 ± 3.03 years. The body mass index (cases 25.84 ± 4.52; controls 25.74 ± 5.0; p > 0.05) and waist-hip ratio (cases 1.06 ± 0.13; controls 1.14 ± 0.2; p > 0.05) were similar in both groups. While fasting serum lipids were not significantly different between the two groups, a number of serum lipid abnormalities were noted in type 2 diabetic subjects in the postprandial state. These included a higher triglyceride-area under curve (AUC) (cases 1298.08 ± 485.2 vs. controls 922.15 ± 390.47 mg/dl/8h; p=0.01), a higher triglyceride-area under incremental curve (AUIC) (cases 549.68 ± 382.24; control 294.75 ± 172.6 mg/dl/8h; p=0.01), a higher peak triglyceride level (cases 425.2 ± 204.47 mg%, controls 283.9 ± 11.6.94 mg%, p=0.01), a lower HDL-AUC (cases 130.35 ± 33.55 vs. controls 168.48 ± 56.01 mg/dl/8h, p=0.013) and a lower HDL nadir (Cases 28.05 ± 10.94 mg%, controls 37.13 ± 13.52 mg%, p < 0.02). Triglyceride AUC correlated significantly with fasting serum triglyceride (r=0.62) and BMI (r=0.7), but not with waist hip ratio . Postprandial lipaemia did not correlate with age, duration of diabetes, fasting blood glucose or glycosylated hemoglobin. Conclusion: In conclusion, type 2 diabetics demonstrate significant postprandial lipid abnormalities, particularly of triglycerides, which appear to be independent of glycaemic control. Journal of Nepalgunj Medical College Vol.13(1) 2015: 21-24